Pengaruh Kompetensi Terhadap Kinerja Karyawan Pada PT. Media Jaya Indonesia Pekanbaru - yulia harwina (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This study aimed to determine the effect of competence on employee performance at PT. Media Jaya Indonesia Pekanbaru. Competence was considered one of the crucial factors that influenced the quality and productivity of employee work. The research method used was quantitative descriptive with an associative approach. The population in this study consisted of all employees of PT. Media Jaya Indonesia Pekanbaru, totaling 44 individuals. Since the population was fewer than 100, the sampling technique used was a census, meaning all members of the population were taken as the research sample. The data analysis techniques included validity and reliability tests, simple linear regression analysis, t-test, and coefficient of determination (R²). The results showed that competence had a positive and significant effect on employee performance. This was evidenced by the t-test result, where the t-count was 8.056, which was greater than the t-table value of 2.018, with a significance value of 0.000 < 0.05, indicating that H₀ was rejected and Hₐ was accepted. The regression equation obtained was Y = 15.566 + 0.846X, meaning that for every one-unit increase in competence, employee performance increased by 0.846 units. The coefficient of determination (R²) was 0.607, indicating that competence contributed 60.7% to employee performance, while the remaining 39.3% was influenced by other variables not examined in this study.